Sistem Pendukung Keputusan Pemilihan Nasabah Prioroitas Untuk Asuransi Davestera Menggunakan Metode PROMETHEE II - Astika Sari Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Davestera Insurance is insurance that provides easy steps to optimize your investment funds. Davestera Insurance is expected to be able to accommodate the needs of younger generation customers for life protection needs as well as long-term investment needs. In choosing a Customer priority for Davestera insurance is very important because we have to look for criteria that are effective in order to get good results. Because priority customers exist if there is loyalty. Decision support system (SPK) is part of a computer-based information system, including a knowledge-based system or knowledge management that is used to support decision making in an organization or company. PROMETHEE is one of the Multi Criteria Decision Making (MCDM) methods, which means making determinations or sequencing in a multi-criteria analysis, this method is known for its efficient and simple concept, in addition to solving problems related to multi criteria, this method is also very easy to be applied than other methods.